Key Success Factors and Motivation Affecting the Care of Patients with Tuberculosis of Health Personnel in Primary Care Units - Phatthraphon Chowong; Prachak Bouphan; Nakarin Prasit; Surachai Phimha (Institute of Medico-legal Publications Pvt Ltd, 2021)
This research is a cross-sectional descriptive aimed to study key success factors and motivation affectingthe care of patients with tuberculosis of health personnel in primary care units Nongbualamphu province,Thailand. The populations were 89 health personnel and 12 key informants. The content validity of thequestionnaire was evaluated by three experts with an IOC greater than 0.50 and Cronbach’s CorrelationCoefficient was 0.97 and In-Depth interview guidelines for the qualitative. Data was collected between 4thJanuary 2021 and 25th January 2021.The results of the study showed that five factors including; 1) motivation factor in responsibility 2)Hygiene Factor in policy and management 3) key success factor in the startup in areas that are ready andwilling to participation 4) Hygiene Factor in a relationship with supervisors, subordinates, co-workers and5) Hygiene Factor in salary and compensation affecting and could joint predict the care for tuberculosispatients in primary care at 75.0 percentage (R2 = 0.750, p-value <0.001). In conclusion, key success factorsand motivation affecting the care of patients with tuberculosis of health personnel in primary care units.Therefore, the health personnel should be developed in terms of work priorities, working process that ledto the intention to work, awareness of their roles and responsibilities Including promoting participation inpolicymaking on tuberculosis work.